Ultrasonographic measurement of the equine fetal vitreous body length for predicting days to parturition in Pura Raza Española horses - Razquin Echeverriarza, Patricio (2019)
Ultrasonographic measurement of the fetal vitreous body length to predict parturition date in horses has shown substantial differences between breeds. PRE (Pura Raza Española or Purebred Spanish Horse) is an important breed in the equine industry of Costa Rica. No data for prediction of parturition exists for PRE using fetal ocular measurements. Between-observer agreement has never been evaluated for fetal ocular measurements on horses. A total of 86 ocular diameters were measured by a veterinarian in twelve PRE mares from day 240 of gestation until parturition. Forty measurements were repeated by a senior veterinary student to determine between-observer agreement. Transrectal ultrasonography was performed in each occasion, and a mean was calculated of the three measurements obtained. Two nonlinear regression equations were derived using days before parturition and age of gestation as dependent variables and vitreous body length as the independent variable. The model obtained for days before parturition was y = 1123.8 -55.5*x+0.689*x2, where “y” represents days before parturition and “x” represents fetal ocular diameter (r2= 0.79; P<0.001); and y = -710.6+51.8*x -0.644*x2, where “y” represents age of gestation and “x” represents ocular diameter (r2= 0.75; P<0.001). Pearson correlation coefficient and paired t-test were performed to assess the between-observer agreement. No significant differences (p=0.86) were detected between-observers, indicating high reproducibility. This study concluded that ocular diameter measurement can be reproduced with high precision by different veterinarians, and either model using days before parturition or age of gestation can be used to predict parturition in PRE mares when breeding dates are unknown